Quality and quantity of domestic wastewater studies and effectiveness of sewage treatment plant at Seberang Perai Jaya,Perai/Mohd Izzaham Ismail - Ismail, Mohd Izzaham (Faculty of Civil Engineering, 2006)
Wastewater generation is something that we should pay more attention to as every individuals and almost everything produce waste such as domestic waste and industrial waste. Since Malaysia is experiencing rapid population growth, the needs to evaluate the quality and quantity of domestic wastewater and the effectiveness of a sewage treatment plant is ought to be necessary. These studies will focused on studying the quality and quantity of domestic wastewater including the effectiveness of a treatment plant which is situated at Seberang Perai Jaya. From the data of influent and effluent obtained from Indah Water Konsortium, the analysis of the quality, quantity and the effectiveness of the domestic wastewater studies will be made. It will be based on the effluent standard from the Department of Environment and in this case, the parameters involved in identifying all the requirements is basically BOD, SS, COD, pH and Ammonia. Based on the effluent standard and the Malaysian Standards Code for the Practice for Design and Installation of Sewerage Systems, which is MS 1228, the determination of quality whether it is normal or not, comply with standards or not and whether it is effective or not, can be done subsequently.